Antiseptic-loaded casein hydrogels for wound dressings - Garcia, Leonor Vasconcelos (2023)
Chronic wound treatment accounts for a substantial percentage of the medical expenses worldwide. Improving and developing novel wound care systems can potentially help to handle this problem. Wound dressings loaded with antiseptics may be an important tool for wound care, as they inhibit bacterial growth at the wound site. The goal of the present work was to investigate the potential of using casein hydrogel dressings loaded with two antiseptic drugs, Octiset® or polyhexanide, to treat chronic wounds. Casein-based hydrogels are inexpensive and have several properties that make them suitable for biomedical applications. Two types of casein were used: casein sodium salt and acid casein, with the formulations being labelled CS and C, respectively. The hydrogels were characterised with respect to their physical properties (swelling capacity, water content, morphology, mechanical resistance, and stability), before and after sterilisation, and they showed adequate values for the intended application. The hydrogels of both formulations were able to sustain controlled drug-release for, at least, 48 h. They were demonstrated to be non-irritant, highly haemocompatible, and non-cytotoxic, and revealed good antimicrobial properties against Staphylococcus aureus and Pseudomonas aeruginosa. Steam-heat sterilisation did not compromise the material’s properties. The in vivo performance of C hydrogel loaded with Octiset® was evaluated in a case study with a dog. The efficient recovery of the wounds confirms its potential as an alternative for wound treatment. To our knowledge, this is the first time that wound dressings loaded with Octiset®, one of the most efficient drugs for wound treatment, were prepared and tested.